SiC and SiOC ceramic articles produced by stereolithography of acrylate modified polycarbosilane systems. Issue 16 (December 2017) - de Hazan, Y.; Penner, D.
Abstract: 3D printed ceramic articles are receiving increased interest recently. Stereolithography (STL) is the method of choice where surface quality, high resolution and high aspect ratio architectures are concerned. Recently, we have developed a UV curable system consisting of allylhydridopolycarbosilane (AHPCS) and multifunctional acrylates. In our present work we investigate the photo-crosslinking mechanism and use selected formulations for the 3D printing of SiC rich ceramic articles using a desktop STL device. High resolution and complex shape articles are demonstrated. The versatile curing method can be used for the STL of practically most other vinyl/allyl modified preceramic polymers. The nano-porosity as well as SiOxCy composition can be tailored in a wide range for specific applications by the ratio of acrylate to AHPCS and by the type of acrylate and AHPCS used.